2019
DOI: 10.3389/fped.2019.00428
|View full text |Cite
|
Sign up to set email alerts
|

Perspective: Using Bronchiectasis Action Management Plans for Children With Bronchiectasis—Can It Improve Clinical Care?

Abstract: While once thought to be rare, bronchiectasis has been increasing globally over the last 15 years. Bronchiectasis is a major contributor to chronic lung morbidity and mortality but remains a neglected disease in respiratory health globally. Currently, few high-level evidence-based management strategies are available for children with bronchiectasis. Strategies to improve clinical outcomes associated with exacerbations are important. In other respiratory conditions such as asthma and chronic obstructive pulmona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…To date there are no studies evaluating an action management plan in children with bronchiectasis [26]. The ERS and ELF have highlighted the need for an action management plan for respiratory exacerbations amongst the highest clinical needs for parents of children with bronchiectasis [7].…”
Section: Discussionmentioning
confidence: 99%
“…To date there are no studies evaluating an action management plan in children with bronchiectasis [26]. The ERS and ELF have highlighted the need for an action management plan for respiratory exacerbations amongst the highest clinical needs for parents of children with bronchiectasis [7].…”
Section: Discussionmentioning
confidence: 99%
“…To date, there are no such studies in children or adults with bronchiectasis. 23 24 A recent systematic review specific to the use of an action plan for bronchiectasis in children confirmed the absence of randomised controlled trials (RCTs). 23 A Cochrane review on self-management in bronchiectasis further highlighted the paucity of evidence in both adults and children, 24 finding only two small poor quality trials in adults using interventions of education and/or rehabilitation, neither with an action plan intervention and highlighted the need for research in children.…”
Section: Introductionmentioning
confidence: 99%
“… 23 24 A recent systematic review specific to the use of an action plan for bronchiectasis in children confirmed the absence of randomised controlled trials (RCTs). 23 A Cochrane review on self-management in bronchiectasis further highlighted the paucity of evidence in both adults and children, 24 finding only two small poor quality trials in adults using interventions of education and/or rehabilitation, neither with an action plan intervention and highlighted the need for research in children. With this major research gap of whether using a personalised BAMP improves clinical outcomes, it is not surprising that a BAMP is not used routinely, even in tertiary centres, when managing children with bronchiectasis.…”
Section: Introductionmentioning
confidence: 99%